Assessment of School Student Achievement in Traditional vs Developmental Education: Psychological and Pedagogical Analysis - Tamara Gordeeva; Oleg Sychev; Anastasia Sidneva (Вопросы образования, 2021)
This study is a theoretical analysis of two student assessment systems that are most common in Russian schools: traditional performance grading and evaluation within the developmental education paradigm proposed by Daniil Elkonin and Vasily Davydov, which implies a set of assessment criteria for different types of achievement, self-assessment, peer assessment, and no focus on assessment results or comparisons. Elementary school students enrolled in traditional and developmental education systems became participants in two empirical studies. Projective techniques (Three Wishes and Three Questions to a Wise Man) were used to measure grades’ related anxiety among third- to fourth-graders in traditional (TE) and developmental classes (DE). Content analysis of children’s spontaneous wishes and questions to a wise man (N(TE) = 327, N(DE) = 153) shows that students in traditional classes are more anxious about their grades than those in developmental classes. In addition, only children in the traditional education system focus on formal assessment at the expense of mastery-based learning outcomes. The second study measured the relationship between grades and academic perseverance, motivation, and self-concept (N(TE) = 309, N(DE) = 78). The value and role of grades may vary in the structure of intrinsic and extrinsic academic motivation and perseverance, as their motivational function differs between the two systems of student assessment. Findings support the idea of organizing school assessments in the logic of developmental education, which is more differentiated, mastery-oriented, and objective. Furthermore, it is originally implemented in cooperation with children, supports the values of enquiry, initiative, independent thinking, and collective discussion, and is less focused on external control and diligence.